2014
DOI: 10.1007/s11284-014-1137-2
|View full text |Cite
|
Sign up to set email alerts
|

Stinging hairs on the Japanese nettleUrtica thunbergianahave a defensive function against mammalian but not insect herbivores

Abstract: Thorns and hairs of plants can serve as defenses against herbivores, although they may not have evolved under selection by herbivory. Japanese nettles, Urtica thunbergiana, in Nara Park, Nara Prefecture, Japan, where sika deer have been protected for 1200 years, bear many more stinging hairs than those in areas with few or no deer. Previous studies suggested that such hairy nettles evolved under natural selection imposed by intense deer browsing, because stinging hairs deterred deer browsing and because among‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Plants that survived such strong selective pressure must have devised some means to protect themselves, and one would expect indications of foliar responses to this herbivory (Iwamoto et al, 2014). The appearance of stinging trichomes in leaves of tribe Urticeae are one example.…”
Section: Discussionmentioning
confidence: 99%
“…Plants that survived such strong selective pressure must have devised some means to protect themselves, and one would expect indications of foliar responses to this herbivory (Iwamoto et al, 2014). The appearance of stinging trichomes in leaves of tribe Urticeae are one example.…”
Section: Discussionmentioning
confidence: 99%
“…Although V. indica larval performance differs between heavily haired NP nettles and lightly haired TCS nettles, V. indica females and larvae do not discriminate between them when allowed to choose at oviposition or feeding (Iwamoto et al. ), indicating a lack of preference–performance linkage. There is also some literature reporting the lack of this linkage in insects (Gripenberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nettles in NP have several dozen times more stinging hairs on leaves than on nettles from surrounding or nearby locations (e.g., TCS), where there are no or few sika deer. The high hair density on nettles in NP is assumed to have evolved as a mechanism to resist deer browsing (Kato et al 2008, Shikata et al 2013, Iwamoto et al 2014).…”
Section: Study Species and Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In NP, several hundred sika deer (Cervus nippon (Artiodactyla, Cervidae) have been protected for more than 1,200 years as sacred animal. Our previous work has revealed that heavily-haired nettles in NP are resistant to sika deer but not herbivorous insects such as the red admiral Vanessa indica (Kato et al 2008;Iwamoto et al 2014) and that variation in hairiness among nettle populations are genetically based (Kato et al 2008;Hirata et al 2019). These ndings suggest that heavy hairiness has evolved through natural selection under intense browsing by sika deer.…”
Section: Introductionmentioning
confidence: 99%